EVALUATION OF GENOTYPES ARISING FROM F2 GENERATION SEGREGATIONS IN DWARF X TALL CROSSES OF COCOSNUCIFERA - WMU Fernando; L. Perera (International Coconut Community Journal, 1997)
Twenty seven F2 generation palms belonging to selfed and crossed families of F1, palms arising from a cross between dwarf green and Tall in Cocos Nucifera were studied for vegetative, reproductive and yield characters. The objective was to study the segregation patterns of the introgressed characters of the Dwarf x Tall hybrid in the F2 generation and, to investigate the effects of selfing. An average of four palms were studied in each F2 family. The time takenfor initial flowering was spread in a greater range in F2 families arising from selfed F1, compared to F2 families originating from crossing two different F1 palms. The pollination behaviour of the palms revealed to be segregating in two selfed F2 families. Two palms, one in each F2 family (selfed F1) were found to be autogamous with overlapping male and female phases whilst the rest showed allogamy. Recombination of the autogamous nature along with the Tall characters were observed in the F2 palms. The results suggest that the genetic control of the pollination behat4our is polygenic and an aggregate of several recessive genes are responsible for the autogamous nature of the palm. Certain genotypes arising from selfed families recorded high husked nut weights (650 ‑ 700 gms) compared to crossed families indicating their resistance to in breeding depression. The possibility of extracting recombined lines with desirable characters in order to improve the Sri Lankan Dwarf x Tall is also discussed